Assessment of emergency contraceptives utilization and associated factors among female college students at Debre Tabor town - Tadesse Wuletaw Demissie; Araya Mesfin Nigatu; Getnet Mihretie Beyene (BMC, 2020)
Abstract Background Unwanted pregnancy is a significant public health problem worldwide. In higher education, students are exposed to the risk of unintended pregnancy, abortion, and its related negative consequences. Objective The objective of this study was to assess the magnitude of emergency contraceptives and factors associated with its utilization among college female students at Debre Tabor Town, Northwest Ethiopia. Methods A cross-sectional, institutional-based study was conducted from June to October 2017. A multi-stage stratified sampling technique was applied to select the study participants. Data were cleaned, coded, and entered into Epi info 7 and exported to SPSS version 20 for analysis. Bivariable and multivariable logistic regression was used to identify the association between the use of emergency contraception and the predictor variables. The P-value less than 0.05 at 95% CI was taken as statistical significance. Results A total of 821 respondents participated with a response rate of 97.6%. The finding showed that 33.3% of them have used emergency contraceptives following unprotected sex. Female students' knowledge about emergency contraceptive [AOR: 2.3; 95% CI 1.20, 4.25], age with 20-24 years category [AOR: 2.3; 95% CI 1.21, 4.49] and married [AOR: 2.8; 95% CI 1.22, 6.21] and divorced [AOR: 4.9; 95% CI 1.12, 21.08] students were found to be significant predictors of EC utilization. Conclusions This study revealed that the level of emergency contraceptive utilization was low. Students' level of knowledge about an emergency contraceptive, age at present, and marital status were found to be the major predictor for emergency contraceptive utilization. Therefore, responsible bodies should develop strategies that enhance the knowledge level of students at the college level on the effective utilization of emergency contraceptive methods.